Evaluation of Adipokines and Metabolic Hormones in Coronary Artery Disease Patients: Association with Inflammatory and Oxidative Stress Biomarkers - Taha, Ziad Tariq (American Journal of Biomedicine and Pharmacy, 2026)
One of the common diseases affecting cardiovascular health is coronary artery disease, which is strongly associated with metabolic disorders, oxidative stress, and inflammation. This study aimed to evaluate the relationship between adipokines and metabolic hormones with markers of inflammation and oxidative stress. The study was conducted at Al-Sharqat General Hospital between January and March 2025, and included 60 patients with coronary artery disease and 30 individuals as a control group. The results showed a significant decrease in the levels of both adiponectin (ADPN) and ghrelin (GHRL) in the patient group compared to the healthy group. Conversely, the levels of leptin (LEP), C-reactive protein (CRP), and malondialdehyde (MDA) were elevated in the patient group compared to the control group. Correlation analysis revealed weak positive correlations between all variables, indicating an interconnected role of metabolic, inflammatory, and oxidative pathways in the development of the disease. The ROC curve analysis also showed strong diagnostic performance for all studied biomarkers, demonstrating their potential usefulness in diagnosing and monitoring the disease.